2022
DOI: 10.1097/paf.0000000000000761
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Fatal Thyroid Hemorrhage After Fine-Needle Aspiration

Abstract: Sudden death due to massive hemorrhage after a mini-invasive ambulatory diagnostic procedure is extremely rare. Fine-needle aspiration (FNA) of thyroid nodules is very safe, displaying a low rate of complications, all of which mild and often self-limiting. In few cases do these complications necessitate surgical decompression, and rarely does FNA of a thyroid nodule lead to the death of the patient.We report a case of sudden death caused by respiratory insufficiency after compression of the vascular and nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In contrast to this, there was no evidence of gross or microhemorrhage in the thyroid tissue or other inciting etiology for the foreign-body reaction seen on histologic evaluation of the thyroid tissue from our patient. Additionally, the foreign-body reaction in our patient's thyroid tissue was focal to the area of the FNA and showed no extension to her perithyroidal tissues or adipose tissue, unlike the case reported by Bonsignore et al Histology findings that would have suggested previous microhemorrhage within the thyroid tissue include the presence of hemosiderin deposits, cholesterol granulomas, and residual fibrin microthrombi in the thyroid vasculature [ 5 ]. There have been reports of post-thyroidectomy foreign-body reactions related to silk sutures used during surgery [ 6 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In contrast to this, there was no evidence of gross or microhemorrhage in the thyroid tissue or other inciting etiology for the foreign-body reaction seen on histologic evaluation of the thyroid tissue from our patient. Additionally, the foreign-body reaction in our patient's thyroid tissue was focal to the area of the FNA and showed no extension to her perithyroidal tissues or adipose tissue, unlike the case reported by Bonsignore et al Histology findings that would have suggested previous microhemorrhage within the thyroid tissue include the presence of hemosiderin deposits, cholesterol granulomas, and residual fibrin microthrombi in the thyroid vasculature [ 5 ]. There have been reports of post-thyroidectomy foreign-body reactions related to silk sutures used during surgery [ 6 ].…”
Section: Discussionmentioning
confidence: 52%
“…The final diagnosis of foreign-body reaction was based entirely on the histology of her thyroid tissue. A case report by Bonsignore et al (2022) [ 5 ] described the case of a 78-year-old woman who experienced fatal thyroid hemorrhage after FNA for a thyroid nodule. In addition to the massive hematoma in the neck seen on autopsy, histology of the thyroid tissue showed a granulomatous process with foreign-body–type giant cells, reactive to colloid extravasation and microhemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, rare but sometimes fatal thyroid hemorrhages after FNAB requiring intubation or surgery have been reported in case reports. Bonsignore et al [35] reported a case of a 78-year-old woman who died due to a massive hematoma leading to tracheal compression and conducted a literature review of 12 cases of fatal thyroid hemorrhages, which were mostly managed with surgery or conservative measures [35][36][37][38][39][40][41][42][43]. Based on the fact that both cases of death identified in the literature review were in older women, the authors stated that increased venous fragility with age and arteriovenous shunts might have contributed to a higher risk of fatal vascular complications [35,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Bonsignore et al [35] reported a case of a 78-year-old woman who died due to a massive hematoma leading to tracheal compression and conducted a literature review of 12 cases of fatal thyroid hemorrhages, which were mostly managed with surgery or conservative measures [35][36][37][38][39][40][41][42][43]. Based on the fact that both cases of death identified in the literature review were in older women, the authors stated that increased venous fragility with age and arteriovenous shunts might have contributed to a higher risk of fatal vascular complications [35,44,45]. It would be advisable to thoroughly investigate the bleeding risk of patients before FNAB, although routine screening for anticoagulants or antithrombotic agents is not mandatory, and Doppler ultrasonography of the thyroid nodule should be performed before the examination, especially for hypervascular nodules and older patients [9].…”
Section: Discussionmentioning
confidence: 99%